Investigation on Metal–Oxide Graphene Field-Effect Transistors With Clamped Geometries - Marco A. Giambra (IEEE, 2019)
In this work, we report on the design, fabrication and characterization of Metal-Oxide Graphene Field-effect Transistors (MOGFETs) exploiting novel clamped gate geometries aimed at enhancing the device transconductance. The fabricated devices employ clamped metal contacts also for source and drain, as well as an optimized graphene meandered pattern for source contacting, in order to reduce parasitic resistance. Our experimental results demonstrate that MOGFETs with the proposed structure show improved high frequency performance, in terms of maximum available gain and transition frequency values, as a consequence of the higher equivalent transconductance obtained.